Spatial Thinking Skills: A Skill Needed to Learn Geology - Chinnawong, Wena; Onthanee, Angkana; Jantakoon, Jakkrit (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2022)
Spatial thinking skills is a necessary skill for understanding of trends and changes that happened between geographical phenomena with time. Which the geographic phenomena can happen from many of reasons. Including the changes of the world which happen all the time. The study of geology will give us to know when the world changes. It will cause trouble to humans and other creatures very quickly. We necessary to study and understand the process of changing the world. We will be prepared to cope with the changes in the world that will occur in the future. Spatial thinking skills will make understand and can connect the relationship of the area with the surrounding area and the effects resulting from changes in the area. We can be analyze, evaluate, prevent and solve problems that arise or predict to occur precisely in order to be safe from geographical phenomena or geological phenomenon. As well as increasing efficiency in solving problems in daily life. It will lead to design and develop useful tools in the field of geology.